An Innovative School Design Based on a Biophilic Approach Using the Appreciative Inquiry Model: Case Study Scandinavia - Amjad Almusaed; Asaad Almssad; Karim Najar (Advances in Civil Engineering)
To understand the school’s role in society and its works, it became essential to reevaluate its functions and importance for society after the aggressive attack of the COVID-19 pandemic. Thus, a new educational space design represents a powerful and required tool for stimulating creativity and increasing concentration, motivation, and assimilation of knowledge for future generations. The article will use appreciative inquiry as a method that works with perspective ideas readings doted by high positive human sensitivity. It also represents a powerful tool for the students’ opinions about the teaching spaces and environments. To improve the performance of educational institutions and schools, considering the sustainability concepts and biophilic designs has become an urgent necessity within the Scandinavian countries and in the world in general. The scientific research and theoretical analysis within the biophilic theory have been conducted to see how the designer can integrate the nature components holistically in the educational environment based on spatial, visual, and ecological integration concepts. The study aims to develop knowledge about applying biophilia as a phenomenon in educational institutes of Scandinavia where the students among others are the main decision-maker. The article’s main finding is that students dream of free open teaching spaces integrated with nature, where the biophilic theory frameworks are suitable to form this sustainable model that enables educational institutions and schools to improve their performance within different stages of the study.